2012
DOI: 10.1111/bjd.12011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and disease severity assessment of epidermolysis bullosa acquisita by ELISA for anti-type VII collagen autoantibodies: an Italian multicentre study

Abstract: This NC1+NC2 ELISA can be a practical assay for the diagnosis of EBA. The correlation between autoantibody titres and disease severity suggests its usefulness as a marker of disease activity in EBA However, this should be confirmed by studies on larger series of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 17 publications
(23 reference statements)
4
27
1
1
Order By: Relevance
“…For our SSS‐positive sera, we found a sensitivity of 80% which is lower than the > 93% found in earlier studies . The three patients who tested negative clinically fitted the diagnosis of mechanobullous EBA.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…For our SSS‐positive sera, we found a sensitivity of 80% which is lower than the > 93% found in earlier studies . The three patients who tested negative clinically fitted the diagnosis of mechanobullous EBA.…”
Section: Discussioncontrasting
confidence: 79%
“…A commercial ELISA is available that has the recombinant NC1 and NC2 coll VII domains coated to the plate, and high sensitivity (> 93%) and specificity (> 96%) have been reported . A correlation between the coll VII ELISA index and disease severity was also demonstrated . Komorowski et al .…”
mentioning
confidence: 99%
“…Based on this insight, the pathogenic relevance of COL7 autoantibodies has been demonstrated (i) in vitro by demonstrating digestion of the dermal–epidermal junction in skin specimen incubated with anti-COL7 IgG or IgA and neutrophils (378, 379), (ii) in vivo by induction of inflammation and blistering in mice by transfer of anti-COL7 IgG (380, 381) or by immunization (382, 383), and (iii) clinically by the observation of a correlation of circulating autoantibody titers with clinical disease severity (384, 385). Subsequently, use of these animal models has greatly contributed to our current understanding of EBA pathogenesis.…”
Section: Autoantibody-induced Inflammationmentioning
confidence: 99%
“…EBA is characterized by autoantibodies of the IgGisotype specific to type VII collagen, the main constituent of anchoring fibrils at the dermal-epidermal junction. 154 Binding of autoantibodies to type VII collagen triggers an inflammatory reaction, including fixation of complement and Fc-dependent activation of leucocytes. 155 Activated granulocytes release reactive oxygen intermediates and proteases leading to epithelial injury and blister formation.…”
Section: Epidermolysis Bullosa Acquisitamentioning
confidence: 99%
“…Recently, an immunoenzymatic method has been set up to detect circulating autoantibodies against type VII collagen. 154 Systemic diseases are often associated with EBA, including CD and, less frequently, UC. 158 A study found that the prevalence of IBD in patients with EBA was about 25%.…”
Section: Epidermolysis Bullosa Acquisitamentioning
confidence: 99%